In search of genuine wine. Origin and consequences of the National Law of Wine of 1904 - Barrio de Villanueva, Patricia (Centro de Historia Argentina y Americana, 2007)
In the context of the wine industry crisis at the beginning of the XXth century arose between the agents implied in that activity a discussion about its causes and possible solutions. One of the changes propitiated was the renovation of legislation that regulated the agricultural industry. This article analyses the genesis of the new wine law, sanctioned in 1904, number 4363, which regulated the activity until the end of the '30 decade and constituted an advancement in the definition of genuine wine and gave to the State tools more than effective to repress the falsification of wine. However, this reinforced the production of wine in mass and left "spaces" of control void that were denounced by other sectors related with the agricultural industry.